Fortifying the foundations for gender in AR4D - Badstue, Lone B. (International Maize and Wheat Improvement Center, 2018)
Presented by Lone Badstue (CIMMYT/GENNOVATE), as part of the Annual Gender Scientific Conference hosted by the CGIAR Collaborative Platform for Gender Research, Addis Ababa, 25-27 September 2018.